СЫНИ ТҰРҒЫДАН ОЙЛАУДЫ ЖАЗБА ЖҰМЫСТАРЫ АРҚЫЛЫ ДАМЫТУ ТӘСІЛДЕРІ - Динаева, Б. Б. ("МӘҢГІЛІК ЕЛДІҢ МӘҢГІЛІК ТІЛІ" Халықаралық симпозиум материалдары, 2016)
Сыни тұрғыдан ойлау стратегиясы бойынша жүргізілетін жұмыста эссе жазу маңызды қызмет атқарады. Эссе мәтіннің мазмұнын сапалы игеруге және күрделі интеллектуалдық-қатысымдық жазбаша пікір айтуға байланысты біліктерді қалыптастыруға мүмкіндік береді... This article describes the methods of application of the technology of critical thinking, as well as an analysis of ways of development of critical thinking through writing. The author focuses on the fact that the use of this technology in the process, students learn different methods of working with the information, learn to articulate their reasoning, to sum up, clearly expressing his opinion, to confirm it with logical arguments, clearly express their thoughts, to be able to carefully listen to his opponent. It is also said that the letter as a form of speech activity is the most effective method of teaching critical thinking.
Keywords: cыни тұрғыдан ойлау стратегиясы; эссе; жазба жұмыстары; Research Subject Categories::HUMANITIES and RELIGION::Languages and linguistics